MAKING PROGRESS: THE AFRICAN COMMITTEE OF EXPERTS ON THE RIGHTS AND WELFARE OF THE CHILD AND THE RIGHTS OF CHILDREN WITH DISABILITIES (African Disability Rights Yearbook, 2021)
The rights of children on the African continent are enshrined within the African Charter on the Rights and Welfare of the Child (ACRWC). This Charter has been ratified by 46 States1 on the continent and, as a result, many states parties to the ACRWC have harmonised their legislative and policy framework in a bid to domesticate the provisions of the Charter as well as other relevant international and regional treaties.2 The African Committee of Experts on the Rights and Welfare of the Child (African Children’s Committee) is established as the body to promote the ratification of the ACRWC and monitor the domestication of this treaty by states parties.3 This subsection provides a brief overview of the ACRWC as the main instrument underpinning the normative framework on the rights of children with disabilities in Africa4 and reports on recent developments in the work of the African Children’s Committee.
Keywords: rights of children; legislative and policy framework; African Committee of Experts on the Rights and Welfare of the Child